Cinderella Complex Behavioral Tendencies - Adawiyah, Robiatul; Rodiyah, Isyatin; Nurhamida, Yuni (Yayasan Adra Karima Hubbi, 2024)
Cinderella complexare women who continue to be psychologically dependent, where women aim to ask for protection from other people, especially men. One of the impacts that occurs is authoritarian parenting. The aim of the researchers is to provide information about one way to reduce the Cinderella complex. The method used is the literature study method, this researcher obtained data sources from various types of literature regarding the Cinderella complex, from this literature discussing the background and problems regarding the Cinderella complex. The study used international and national journals from the journal publication years 2017-2024. The researcher did not collect literature regularly, but did it randomly and searched through the Google database and Google Scholar, the writing also used various keywords to get relevant topics, apart from that the researcher also checked the reference list to look for relevant library sources. was found. The results regarding the behavioral tendencies of the Cinderella complex often view themselves as someone who has deficiencies both mentally, physically and intelligently, making it difficult to be productive. Women who experience the Cinderella complex want help from someone, especially men as a supporter, as well as the presence of men. Men can entertain when women are unable and can be an economic resource in the future.